Keynes et Sraffa - Asimakopulos, A. (L'Actualité économique, 1982)
AbstractKeynes' General Theory of Employment, Interest and Money and Sraffa's Production of Commodities by Means of Commodities were concerned with different problems, and this is reflected in the structure of the models they used. Keynes was concerned with the factors determining the level of employment in a particular period of time — a short period — and the ways in which that level of employment could be thanged over a sequence of these short periods. There is great scope for disappointment of expectations and uncertainty in his analysis — it is not tied in any way to long-period equilibrium. Sraffa's analysis was concerned with highly abstract theoretical questions — the value nature of capital and the lack of logical foundations for any marginal productivity theory of distribution that treats aggregate capital as an input. For this purpose, an analysis solely concerned with long-period equilibrium situations is not inappropriate. In these works there is no meeting ground between Sraffa and Keynes. The joining of the two analyses — except as a very special case in which entrepreneurial investment-expectations turned out to be validated by events — would distort seriously the nature of Keynes' analysis.